2018
DOI: 10.1159/000494875
|View full text |Cite
|
Sign up to set email alerts
|

Expression Signature and Role of miR-30d-5p in Non-Small Cell Lung Cancer: a Comprehensive Study Based on in Silico Analysis of Public Databases and in Vitro Experiments

Abstract: Background/Aims: The purpose of this study was to probe the clinico-pathological significance and the underlying mechanism of miR-30d-5p expression in non-small cell lung cancer (NSCLC). Methods: We initially examined the level of miR-30d-5p expression in NSCLC and non-cancer tissues using RT-qPCR. Then, a series of validation analyses including a meta-analysis of data from microarray chips in Gene Expression Omnibus (GEO), data mining of the cancer genome atlas (TCGA) and an integrated meta-analysis incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…miR-30d belongs to the miR family and is located on human chromosome 8q24.22. More and more studies have found that miR-30d is low expressed in various tumors such as lung cancer, 26 colon cancer 27 and ovarian cancer. 28 Moreover, the biological function can be reversed by upregulating miR-30d.…”
Section: Discussionmentioning
confidence: 99%
“…miR-30d belongs to the miR family and is located on human chromosome 8q24.22. More and more studies have found that miR-30d is low expressed in various tumors such as lung cancer, 26 colon cancer 27 and ovarian cancer. 28 Moreover, the biological function can be reversed by upregulating miR-30d.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the miRNAs targeting the COVID-19 genome showed low abundance (down-regulated) with some underlying conditions ( Table 7). For example, miR-15b-5p (Coronary artery disease) [37], miR-15a-5p (Kidney disease) [38], miR-520c-3p (obesity/diabetes) [39], miR-30e-3p (Myocardial Injury) [40], miR-23c (hepatocellular carcinoma) [41], miR-30d-5p (non-small cell lung cancer) [42], miR-4684-3p (colorectal cancer) 43], and miR-518a-5p (Gastrointestinal stromal tumors) [44] down-regulated in pathophysiological condition.…”
Section: And Supplementarymentioning
confidence: 99%
“…Expression data of PLK1 from microarrays were extracted and processed as described before (Gao et al, 2018;Yang et al, 2018). The standardized mean difference (SMD) and 95% confidence interval (CI) of PLK1 expression between cervical cancer and non-cancer samples were calculated for all included microarrays and RNA-seq datasets, with the methods of random-effect model of meta package in R software v.3.6.1.…”
Section: Verification From External Microarrays and Rna-seq Datasetsmentioning
confidence: 99%